TiO2 supported high-entropy alloy biomass carbon fiber composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611507936.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]针对现有锂硫电池隔膜改性材料存在的高熵合金负载稳定性差、碳材料吸附能力不足、催化活性位点单一等问题,本发明提供一种二氧化钛(TiO2)负载高熵合金/生物质碳纤维复合材料及其制备方法,提出以TiO2作为高熵合金(HEA)的锚定基底
[0035](1)本发明构建了碳纤维导电骨架、TiO2吸附/锚定层和HEA催化层三层一体化结构,实现了物理限域、化学吸附和催化转化三重协同机制。其中,生物质碳纤维的三维交织多孔结构对多硫化物提供物理限域和快速电子传输;TiO2通过Ti-S键对多硫化物提供强化学吸附,并作为HEA的锚定基底;高熵合金通过多金属协同效应提供高效的催化转化能力。三者缺一不可,协同实现对多硫化锂的全链条管控。本发明中TiO2不仅作为极性吸附剂,更关键的是作为高熵合金的锚定基底和电子结构调控层。TiO2表面丰富的氧原子为高熵合金纳米颗粒提供M-O键锚定位点,实现高熵合金的原位外延生长和牢固负载。同时,TiO2与HEA之间的功函数差异驱动界面电荷转移,精确调控HEA的d带中心位置,优化催化活性。这一设计解决了传统碳负载高熵合金中颗粒易团聚、电子结构不可调的技术难题。
Smart Images

Figure CN123018345A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a titanium dioxide (TiO2) supported high-entropy alloy biomass carbon fiber composite material suitable for lithium-sulfur battery separator modification, its preparation method, and its application. Background Technology
[0002] Lithium-sulfur batteries, with their high theoretical specific capacity of 1675 mAh / g and theoretical energy density of 2600 Wh / kg, coupled with the advantages of abundant sulfur resources, low cost, and environmental friendliness, are considered strong contenders for the next generation of high-energy-density electrochemical energy storage systems. However, the practical application of lithium-sulfur batteries still faces many technical bottlenecks, mainly including: the extremely low electronic conductivity of sulfur and its discharge products (Li2S / Li2S2), resulting in low utilization of active materials; the volume expansion of sulfur during charging and discharging can reach 80%, easily causing damage to the electrode structure; and the "shuttle effect" of intermediate soluble lithium polysulfides (LiPSs) between the positive and negative electrodes, leading to loss of active materials, reduced coulombic efficiency, and rapid capacity decay.
[0003] Membrane functionalization is widely considered an effective strategy for suppressing the shuttle effect and improving sulfur conversion kinetics. Traditional polyolefin membranes (such as PP and PE) can only achieve physical isolation and cannot prevent the migration of polysulfides. Therefore, researchers have attempted to coat various functional materials onto the membrane surface to endow the membrane with the ability to adsorb and catalytically convert polysulfides. Carbon-based materials (such as carbon nanofibers and graphene) have been extensively studied due to their high conductivity and porous structure; however, the interaction between nonpolar carbon materials and polar polysulfides mainly relies on weak van der Waals forces, resulting in limited adsorption capacity. Polar oxides (such as TiO2, Al2O3, and SiO2) have strong chemisorption effects on polysulfides, among which TiO2 is considered a promising membrane modification material due to its excellent chemical stability and catalytic activity. However, the catalytic active sites of TiO2 alone are limited, making it difficult to meet the kinetic requirements of multi-step polysulfide conversion reactions.
[0004] In the preparation of carbon fiber substrates, while electrospinning can obtain nanofibers with uniform diameter, it is costly and difficult to achieve high-value utilization of waste biomass resources. Wet papermaking technology, as a mature fiber forming process, can prepare natural biomass fibers into fiber sheets with a three-dimensional interwoven network structure, which are then carbonized to obtain carbon fiber materials with a through-pore structure. However, the conductivity and catalytic activity of existing paper-based carbon fiber materials are still insufficient to meet the requirements of high-performance lithium-sulfur batteries.
[0005] In recent years, high-entropy alloys (HEAs), as a novel class of alloy materials composed of five or more metallic elements, have shown great potential in the field of electrocatalysis due to their multi-component synergistic effect, lattice distortion effect, and tunable electronic structure. Previous studies have used HEAs nanoparticles loaded onto carbon fibers as an interlayer in lithium-sulfur batteries, achieving good battery performance. However, in existing technologies, HEAs are usually directly loaded onto the surface of carbon materials. Because the carbon surface lacks strong bonding sites with metal ions, the nanoparticles are prone to agglomeration and exhibit poor loading stability. More importantly, directly loading HEAs onto the carbon surface prevents the use of heterojunction effects to modulate the electronic structure of the alloy. Summary of the Invention
[0006] To address the problems of poor high-entropy alloy loading stability, insufficient carbon material adsorption capacity, and limited catalytic active sites in existing lithium-sulfur battery separator modification materials, this invention provides a titanium dioxide (TiO2)-supported high-entropy alloy / biomass carbon fiber composite material and its preparation method, proposing to use TiO2 as the anchoring substrate for the high-entropy alloy (HEA). The TiO2 surface is rich in oxygen atoms, enabling strong chemical bonding with high-entropy alloy nanoparticles through metal-oxygen bonds, achieving in-situ epitaxial growth of the high-entropy alloy and significantly improving loading stability. Simultaneously, the work function difference between TiO2 and the high-entropy alloy can induce interfacial charge transfer, regulating the d-band center position of the high-entropy alloy, thereby optimizing its adsorption energy and catalytic activity for lithium polysulfides. The papermaking biomass carbon fiber, TiO2 anchoring layer, and high-entropy alloy catalytic layer are integrated into a single structural design and applied to a lithium-sulfur battery separator modification technique. The TiO2 intermediate layer achieves robust anchoring and electronic structure regulation of the high-entropy alloy, and the triple synergistic mechanism significantly improves the performance of lithium-sulfur batteries.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A TiO2-supported high-entropy alloy biomass carbon fiber composite material, comprising:
[0009] Biomass-based porous carbon fiber is prepared from natural biomass fiber slurry through wet papermaking and high-temperature carbonization, and has a three-dimensional interconnected porous conductive network structure.
[0010] TiO2 nanoparticle layer is uniformly loaded on the surface of the biomass carbon fiber, forming a TiO2 / C heterostructure interface with the carbon fiber.
[0011] High-entropy alloy nanoparticles are grown in situ on the surface of TiO2 nanoparticles and bonded to oxygen atoms in the TiO2 lattice through metal-oxygen bonds to form a TiO2 / HEA heterostructure interface.
[0012] The high-entropy alloy contains at least five transition metal elements and is a single-phase solid solution with a face-centered cubic or body-centered cubic structure.
[0013] This invention uses a wet papermaking process to prepare biomass carbon fiber, which has the following advantages compared with the electrospinning method: (1) The raw materials are widely available and inexpensive, and waste biomass resources such as wood scraps and crop straw can be utilized; (2) The papermaking process is mature and can be scaled up, making it easy to achieve industrialization; (3) The resulting fiber paper has a natural three-dimensional interwoven network structure. After carbonization, the fibers are interconnected to form a continuous conductive path, and the micron-level through-holes formed by the interwoven fibers are conducive to electrolyte wetting and ion transport.
[0014] In this invention, TiO2 nanoparticles loaded on the surface of carbon fibers play the following key roles: (1) TiO2, as a polar oxide, provides chemical adsorption of polysulfides through Ti-S bonds; (2) The surface of TiO2 is rich in oxygen atoms, providing sufficient anchoring sites for high-entropy alloy nanoparticles. During the reduction process, metal ions form MO bonds with the oxygen in the TiO2 lattice, realizing the in-situ epitaxial growth of high-entropy alloys; (3) The difference in work function between TiO2 and high-entropy alloys drives the interfacial charge transfer, regulates the electronic structure of high-entropy alloys, and optimizes their catalytic activity.
[0015] In this invention, high-entropy alloy nanoparticles are grown in situ on the surface of TiO2. They are firmly anchored to the TiO2 lattice oxygen atoms through strong metal-oxygen bonds (MO bonds), effectively preventing particle detachment and agglomeration during charging and discharging. Simultaneously, the work function difference between TiO2 and the high-entropy alloy drives directional electron transfer at the TiO2@HEA heterojunction, precisely controlling the d-band center position of the high-entropy alloy, optimizing the adsorption energy for lithium polysulfide intermediates, reducing the energy barriers of each conversion reaction, and significantly improving the kinetic performance of the sulfur reduction reaction (SRR) and sulfur precipitation reaction (SER).
[0016] Furthermore, the biomass fiber pulp is derived from at least one of wood scraps, crop straw, bamboo pulp, hemp pulp, or cotton pulp; the biomass carbon fiber has a hierarchical pore structure with micron-level through-holes formed by fiber interlacing and micropores / mesopores coexisting, generated during the carbonization process.
[0017] Furthermore, the TiO2 nanoparticles have a crystal form of anatase, rutile, or a mixture of both phases.
[0018] Furthermore, the high-entropy alloy contains five elements: Ni, Co, Fe, Mn, and Zn; the average particle size of the high-entropy alloy nanoparticles is 2~20 nm.
[0019] The above-mentioned method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material includes the following steps:
[0020] S1. Mix biomass fiber pulp with water, and after pulping, loosening, screening and removing impurities, add NaOH solution and stir for a period of time. After the end, wash thoroughly with deionized water to obtain biomass fiber filter cake.
[0021] S2. Surface modification of TiO2: TiO2 powder is mixed with H2O2 and refluxed in a water bath at a certain temperature for a period of time. After the reaction is completed, the mixture is washed to obtain modified TiO2 precipitate.
[0022] S3. Disperse the modified TiO2 precipitate obtained in step S2 in a precursor solution containing at least five transition metal salts, and stir thoroughly to obtain a mixed slurry.
[0023] S4. The biomass fiber filter cake obtained in step S1 is placed into the mixed pulp obtained in S3 and stirred thoroughly to make it evenly mixed. The mixed pulp obtained above is dewatered and formed by wire section and pressed to obtain composite fiber wet paper sheet by using wet paper forming process.
[0024] S5. After drying the composite fiber wet paper obtained in S4, it is subjected to high-temperature heat treatment in a reducing atmosphere to reduce and alloy the metal salt in situ on the TiO2 surface. The high-entropy alloy nanoparticles are epitaxially grown on the TiO2 surface through metal-oxygen bonds to obtain TiO2-loaded high-entropy alloy / biomass carbon fiber composite material.
[0025] The in-situ growth mechanism of high-entropy alloys on TiO2 surfaces is as follows: After impregnation of TiO2 with a transition metal salt solution, metal ions (Mⁿ⁺) form MO coordination bonds with oxygen atoms in the TiO2 surface lattice and are uniformly anchored on the TiO2 surface. Under a high-temperature reducing atmosphere, the metal ions are reduced to zero-valent metal atoms. Using the anchoring points on the TiO2 surface as nucleation centers, the metal atoms diffuse and alloy with each other at the nanoscale, ultimately growing into high-entropy alloy nanoparticles. Simultaneously, the work function difference between TiO2 and the high-entropy alloy drives the redistribution of interfacial electrons, forming a TiO2 / HEA heterointerface with an optimized electronic structure, further enhancing catalytic activity.
[0026] Further, in step S1, the concentration of the NaOH solution is 0.5~2 mol / L, and the stirring time is 6~10 h; the solid-liquid ratio of the biomass fiber pulp to the NaOH solution is 1:10~1:30 g / mL.
[0027] Further, in step S2, the mass fraction of H2O2 is 30 wt%, and the solid-liquid ratio of TiO2 powder to H2O2 is 1:10~1:50 g / mL; the temperature of the water bath reflux reaction is 60~80℃, and the reaction time is 4~8 h.
[0028] Further, the transition metal salts mentioned in step S3 are chloride salts, nitrate salts, or acetylacetone salts of various metals; the molar ratio of at least five transition metal salts is an equimolar ratio or a near-equimolar ratio; and the solvent of the precursor solution is at least one of water, ethanol, N,N-dimethylformamide, or ethylene glycol.
[0029] Furthermore, the precursor solution in step S3 also contains an organic ligand, which is at least one of 2,5-dihydroxyterephthalic acid (H4DHTP), 2-methylimidazolium, or trimesic acid; after the modified TiO2 precipitate is added to the precursor solution, it is reacted at 80~150℃ for 12~48 h to allow the metal ions and organic ligand to coordinate and self-assemble on the TiO2 surface to form a MOF precursor.
[0030] Further, the wet papermaking process in step S4 is as follows: after the mixed pulp is evenly distributed by the pulp distributor, it is dewatered and formed under the vacuum suction of the wire section, and then pressed and dewatered by the press roller under a pressure of 0.2~0.5 MPa to obtain a composite fiber wet paper sheet; the drying temperature is 60~120℃ and the drying time is 6~24 h.
[0031] Furthermore, the high-temperature heat treatment described in step S5 is a segmented annealing process, including: the first stage: heating to 150-250℃ at 1-5℃ / min and holding for 0.5-2 h; the second stage: heating to 350-450℃ at 1-5℃ / min and holding for 1-3 h; the third stage: heating to 600-1000℃ at 1-5℃ / min and holding for 2-6 h; each stage is carried out in an argon atmosphere or an argon / hydrogen mixed atmosphere.
[0032] The present invention also provides an application of TiO2-supported high-entropy alloy biomass carbon fiber composite material in lithium-sulfur battery separators, wherein the lithium-sulfur battery separator comprises: a polyolefin-based separator, and a functional coating coated on at least one surface of the base separator; the functional coating comprises the aforementioned TiO2-supported high-entropy alloy biomass carbon fiber composite material.
[0033] Furthermore, the functional coating also includes a conductive agent and a binder, and the mass ratio of the composite material, the conductive agent and the binder is (6~9):(1~2):(1~2); the thickness of the functional coating is 100~200 μm.
[0034] The beneficial effects of this invention are as follows:
[0035] (1) This invention constructs a three-layer integrated structure consisting of a carbon fiber conductive framework, a TiO2 adsorption / anchoring layer, and a HEA catalytic layer, achieving a triple synergistic mechanism of physical confinement, chemical adsorption, and catalytic conversion. Specifically, the three-dimensional interwoven porous structure of biomass carbon fibers provides physical confinement and rapid electron transport for polysulfides; TiO2 provides strong chemical adsorption of polysulfides through Ti-S bonds and serves as the anchoring substrate for HEA; and the high-entropy alloy provides efficient catalytic conversion through multi-metal synergistic effects. All three are indispensable, working together to achieve full-chain control of lithium polysulfides. In this invention, TiO2 not only acts as a polar adsorbent but, more importantly, serves as the anchoring substrate and electronic structure regulation layer for the high-entropy alloy. The abundant oxygen atoms on the TiO2 surface provide MO bond anchoring sites for the high-entropy alloy nanoparticles, enabling in-situ epitaxial growth and robust loading of the high-entropy alloy. Simultaneously, the work function difference between TiO2 and HEA drives interfacial charge transfer, precisely controlling the d-band center position of HEA and optimizing catalytic activity. This design solves the technical problems of easy particle agglomeration and untunable electronic structure in traditional carbon-loaded high-entropy alloys.
[0036] (2) Compared with electrospinning, the wet papermaking process used in this invention has advantages such as a wide range of raw material sources (agricultural and forestry waste can be used), low cost, and large-scale production. The interwoven network between natural biomass fibers forms a continuous conductive path after carbonization, and the micron-level through-pores formed by the interwoven fibers are conducive to electrolyte wetting and ion transport.
[0037] (3) In this invention, the high-entropy alloy nanoparticles are firmly anchored to the TiO2 surface through metal-oxygen bonds, effectively preventing particle shedding and agglomeration during charging and discharging, and ensuring long-term cycle stability. At the same time, the TiO2 intermediate layer acts as a buffer layer, alleviating the structural stress caused by the difference in thermal expansion coefficients between the carbon fiber and the high-entropy alloy. Attached Figure Description
[0038] Figure 1 The image shows a scanning electron microscope (SEM) image of the composite material obtained in Example 1.
[0039] Figure 2 This is a high-magnification scanning electron microscope (SEM) image of the composite material obtained in Example 1;
[0040] Figure 3 The first charge-discharge curves of the lithium-sulfur battery assembled using the composite material obtained in Example 1 as a separator coating are shown at rates of 0.1 to 2C.
[0041] Figure 4 The rate performance curves of lithium-sulfur batteries assembled using the composite materials obtained in Example 1 and Comparative Examples 1 and 2 as separator coatings are shown.
[0042] Figure 5The rate performance curve of the lithium-sulfur battery assembled as a separator coating in Example 2;
[0043] Figure 6 The image shows the cycle performance curves of lithium-sulfur batteries assembled using the composite materials obtained in Example 1 and Comparative Examples 1 and 2 as separator coatings. Detailed Implementation
[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] Example 1
[0046] This embodiment provides a method for preparing TiO2-supported high-entropy alloy biomass carbon fiber composite material, including the following steps:
[0047] S1. Alkali activation treatment of biomass fiber.
[0048] Using crop straw as biomass raw material, the straw is crushed and ground into coarse fiber, then pulped with water and impurities are removed to obtain raw pulp. 10 g of the raw pulp (based on oven-dry fiber) is added to 200 mL of a 1 mol / L NaOH solution and stirred at 300 r / min for 8 h at room temperature to allow the fibers to fully swell and activate their surface. After stirring, the solution is repeatedly filtered and washed with deionized water until the filtrate is neutral (pH≈7), yielding a biomass fiber filter cake.
[0049] S2 and TiO2 surface hydroxylation modification.
[0050] 2 g of TiO2 powder was added to 100 mL of 30% H2O2 solution and refluxed in an 80℃ water bath for 6 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and centrifuged at 8000 r / min to obtain the precipitate. The precipitate was washed three times with deionized water to obtain the modified TiO2 precipitate.
[0051] S3. Preparation of multi-metal precursor solutions and formation of metal-organic framework (MOF) precursors.
[0052] The modified TiO2 precipitate obtained in step S2 was dispersed in 35 mL of an N,N-dimethylformamide (DMF) solution containing equimolar amounts (2 mmol each) of Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Mn(NO3)2·4H2O, Zn(NO3)2·6H2O, and FeSO4·5H2O, and stirred until homogeneous. 0.797 g of 2,5-dihydroxyterephthalic acid (H4DHTP) was added (the molar ratio of total metal salt to ligand was approximately 1:4), and stirring continued for 30 min. The mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene and reacted at 120 °C for 24 h, allowing the metal ions and the organic ligand H4DHTP to coordinate and self-assemble on the TiO2 surface to form a MOF precursor. After the reaction, the mixture was naturally cooled to room temperature to obtain a modified slurry containing the TiO2@multimetal MOF precursor.
[0053] S4, Wet papermaking
[0054] The biomass fiber filter cake obtained in step S1 is added to the modified slurry obtained in step S3, and stirred for 1.5 h to ensure thorough mixing. The mixed slurry is then processed using a wet papermaking process: after being evenly distributed by a slurry distributor, the slurry is dewatered and shaped under vacuum suction at the wire section, and then pressed and dewatered by press rolls at a pressure of 0.3 MPa to obtain a composite fiber wet paper sheet. The wet paper sheet is then dried in an 80℃ oven for 12 h to obtain biomass-based porous carbon fibers.
[0055] S5, Segmented annealing and carburization with in-situ growth of high-entropy alloy (HEA)
[0056] The dried biomass-based porous carbon fibers obtained in step S4 are cut into appropriate sizes and placed in a tube furnace for segmented annealing in an argon / hydrogen (95 / 5 v / v) mixed atmosphere.
[0057] First stage: Increase the temperature to 200℃ at a rate of 3℃ / min and hold for 1 hour;
[0058] Second stage: Increase the temperature to 400 ℃ at 3 ℃ / min and hold for 2 h;
[0059] Third stage: Increase the temperature to 800 ℃ at a rate of 2 ℃ / min and hold for 4 h.
[0060] After the temperature naturally drops below 50 ℃, the material is removed to obtain a TiO2-loaded high-entropy alloy / biomass carbon fiber composite material, denoted as TiO2@HEA / PCF-1.
[0061] This embodiment describes the application and testing of TiO2@HEA / PCF-1 material as a membrane modification material.
[0062] The prepared TiO2@HEA / PCF-1 material, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) were mixed and ground uniformly in 1-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 8:1:1. The slurry was then coated onto a polypropylene separator (PP, Celgard 2400) using a coater and transferred to a vacuum oven to dry at 60°C for 12 hours. The separator was then cut into 20mm diameter discs for subsequent coin cell assembly.
[0063] Example 2
[0064] The difference between this embodiment and Example 1 is that in step S3, the N,N-dimethylformamide (DMF) solution is replaced with a methanol solution, the organic ligand H4DHTP is replaced with 2-methylimidazole, the amount added is 4.0 g (the molar ratio of the total amount of metal salt to the ligand is approximately 1:2), the reaction temperature is adjusted to 140℃, and the reaction time is adjusted to 16 h.
[0065] The remaining steps are the same as in Example 1. The resulting product is denoted as TiO2@HEA / PCF-2. The modified membrane preparation is the same as in Example 1.
[0066] Comparative Example 1
[0067] The difference between this comparative example and Example 1 is that: in step S3, TiO2 is not added, that is, the multi-metal MOF precursor is directly synthesized in DMF solution, and then combined with activated fiber to form a high-entropy alloy / biomass carbon fiber composite material (without TiO2 intermediate layer). The resulting product is denoted as HEA / PCF-1.
[0068] Comparative Example 2
[0069] The difference between this comparative example and Example 1 is that no multi-metal raw materials are added in step S3, and then it is composited with activated fibers to obtain TiO2 / biomass carbon fiber composite material (without high entropy alloy). The resulting product is denoted as TiO2 / PCF-1.
[0070] The material described in Example 1 was characterized using a scanning electron microscope, and the test results are as follows: Figure 1 As shown, the biomass-derived carbon fibers retain their natural fibrous morphology well, with diameters ranging from 2 to 10 μm. These fibers interconnect to form a three-dimensional interwoven network, a typical feature of wet papermaking processes. This interconnected structure provides a continuous electron transport path and facilitates electrolyte permeation. High-magnification SEM images ( Figure 2 The results show that the carbon fiber surface is rough and has TiO2 nanoparticles and HEA nanoparticles evenly distributed.
[0071] The modified separators and blank separators (PP) prepared in Examples 1, 2, 1, and 2 were respectively assembled into five button batteries in a glove box with a positive electrode (made by coating aluminum foil with carbon / sulfur composite slurry), a negative electrode (lithium sheet), and an electrolyte (a non-aqueous electrolyte containing 1 M lithium bis(trifluoromethanesulfonate) in a 1,3-epoxypentane / ethylene glycol dimethyl ether solution (volume ratio 1:1), with 2% LiNO3 added as an additive). The electrochemical performance of these five battery sets was then tested. The electrochemical test results of the five battery sets are as follows: Figure 3 , 4 As shown in Figures 5 and 6, the lithium-sulfur battery using the composite material obtained in Example 1 as the separator modification material exhibits excellent electrochemical performance.
[0072] Figure 3 The image shows the first charge-discharge curves of a lithium-sulfur battery assembled using the composite material obtained in Example 1 as a separator coating, at rates of 0.1–2C. From... Figure 3 As can be seen, the discharge plateau decreases while the charging plateau increases with increasing current. This phenomenon is caused by the increasing polarization of the battery's internal structure with increasing current. However, even at high currents up to 2 C, the discharge curve still exhibits two typical discharge plateaus.
[0073] Figure 4 The rate performance curves of lithium-sulfur batteries assembled with the composite materials obtained in Example 1, Comparative Example 1, and Comparative Example 2 as separator coatings and lithium-sulfur batteries assembled with blank separators are shown. As can be seen from the figure, the composite material obtained in Example 1 has the highest discharge specific capacity at all rates. Its discharge specific capacity at 0.1~2C rates is 1487.3, 1371.7, 1177.4, 1019.4, and 800.4 mAh / g, respectively. Moreover, when the current recovers to 0.2C, its discharge specific capacity is also basically recovered, showing good reversibility and highlighting the structural stability of the composite material. Figure 5 The rate performance curves of the lithium-sulfur battery assembled using the composite material obtained in Example 2 as a separator coating are shown. As can be seen from the figure, its discharge specific capacity at rates from 0.1 to 2C is 1279.2, 972.7, 774.2, 658.9, and 485.6 mAh / g, respectively. At low currents, its discharge specific capacity is comparable to that of the battery based on Example 1, but at high currents, its discharge capacity is significantly lower than that of the battery in Example 1, indicating that the battery in Example 1 has better rate performance. In addition to rate performance, the cycle performance of the four battery groups under high current was also evaluated. Figure 6As shown, the performance of the four battery groups was compared after 1000 charge-discharge cycles at a 2C rate. The battery based on the composite material obtained in Example 1 maintained a capacity of 360 mAh / g after 1000 cycles, demonstrating excellent cycle performance. In contrast, the batteries using Comparative Examples 1 and 2 showed significantly lower performance than the battery assembled with the modified separator prepared in Example 1. This indicates that the integrated structural design of papermaking biomass carbon fiber, TiO2 anchoring layer, and high-entropy alloy catalyst layer, applied to the modification of lithium-sulfur battery separators, achieves robust anchoring and electronic structure regulation of the high-entropy alloy through the TiO2 intermediate layer, and significantly improves lithium-sulfur battery performance through a triple synergistic mechanism.
[0074] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material, characterized in that, Includes the following steps: S1. Mix biomass fiber pulp with water, and after pulping, loosening, and screening to remove impurities, add NaOH solution and stir to make the biomass fiber swell and surface activate; after completion, wash with deionized water to obtain biomass fiber filter cake. S2. Mix TiO2 with H2O2 solution and reflux the reaction in a water bath. After the reaction is complete, wash to obtain modified TiO2 precipitate. S3. Disperse the modified TiO2 precipitate in a precursor solution containing at least 5 transition metal salts, and stir thoroughly to obtain a modified slurry; S4. Wet papermaking process: The biomass fiber filter cake is added to the modified pulp and stirred evenly. The mixed pulp is dewatered and formed by wire section and pressed to obtain composite fiber wet paper sheets and then dried. S5. The dried composite paper is subjected to high-temperature segmented annealing in a reducing atmosphere to obtain TiO2-loaded high-entropy alloy biomass carbon fiber composite material.
2. The method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 1, characterized in that, The concentration of the NaOH solution in S1 is 0.5~2 mol / L, and the stirring time is 6~10 h; the solid-liquid ratio of the biomass fiber pulp to the NaOH solution is 1:10~1:30 g / mL.
3. The method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 1, characterized in that, The mass fraction of H2O2 in S2 is 30wt%, and the solid-liquid ratio of TiO2 powder to H2O2 is 1:10~1:50 g / mL; the reflux reaction temperature is 60~80℃, and the reaction time is 4~8 h.
4. The method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 1, characterized in that, The transition metal salt is a chloride, nitrate, or acetylacetone salt of each transition metal; the molar ratio of at least five transition metal salts is equimolar or nearly equimolar; the solvent of the precursor solution is at least one of water, ethanol, N,N-dimethylformamide, or ethylene glycol.
5. The method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 1, characterized in that, The precursor solution in S3 further contains an organic ligand, which is at least one of 2,5-dihydroxyterephthalic acid (H4DHTP), 2-methylimidazole, or trimesic acid; after the modified TiO2 precipitate is added to the precursor solution, it is reacted at 80-150°C for 12-48 h.
6. The method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 1, characterized in that, The wet papermaking process is as follows: after the mixed pulp is evenly distributed by the pulp distributor, it is dewatered and formed under the vacuum suction of the wire section, and then pressed and dewatered by the press rollers under a pressure of 0.2~0.5 MPa to obtain a composite fiber wet paper sheet; the drying temperature is 60~120℃ and the drying time is 6~24 h.
7. The method for preparing a TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 1, characterized in that, The segmented annealing process specifically involves: First stage: Increase the temperature to 150-250℃ at a rate of 1-5℃ / min, and hold for 0.5-2 hours; Second stage: Increase the temperature to 350-450℃ at a rate of 1-5℃ / min, and hold for 1-3 hours; Third stage: Increase the temperature to 600-1000℃ at a rate of 1-5℃ / min, and hold for 2-6 hours; Each stage is carried out in an argon atmosphere or an argon / hydrogen mixture.
8. A TiO2-supported high-entropy alloy biomass carbon fiber composite material, characterized in that, The TiO2-loaded high-entropy alloy biomass carbon fiber composite material was prepared by any one of claims 1-7.
9. The TiO2-supported high-entropy alloy biomass carbon fiber composite material according to claim 8, characterized in that, The composite material includes: Biomass-based porous carbon fibers have a three-dimensional interconnected porous conductive network structure; TiO2 nanoparticle layer is uniformly loaded on the surface of the biomass carbon fiber, forming a TiO2 / C heterostructure interface with the carbon fiber. High-entropy alloy nanoparticles are grown in situ on the surface of TiO2 nanoparticles and bonded to TiO2 lattice oxygen atoms through metal-oxygen bonds to form a TiO2 / HEA heterostructure interface; the high-entropy alloy contains at least five transition metal elements and is a single-phase solid solution with a face-centered cubic or body-centered cubic structure.
10. The application of the TiO2-supported high-entropy alloy biomass carbon fiber composite material as described in claim 9 in lithium-sulfur battery separators, characterized in that, The lithium-sulfur battery separator includes a polyolefin-based separator and a functional coating coated on at least one surface of the base separator, wherein the functional coating comprises the TiO2-loaded high-entropy alloy biomass carbon fiber composite material.
